Plotinus and Proclus on the Life of Intellect. - MAKSELIS, RASIUS (Logos: A Journal, of Religion, Philosophy Comparative Cultural Studies & Art (08687692), 2021)
The article is devoted to the analysis of the philosophical notion of the “life of Intellect“ as presented by Plotinus and Proclus – representatives of philosophical tradition of Neoplatonism. Different interpretations of the notion of the “life of Intellect,” presented by prominent scholars of 20th century Piere Hadot and A. H. Armstrong, require wider discussion of the concepts of “life” and “intellect” with clearer emphasis on their connections to such Neoplatonic concepts as “well being”, “contemplation”, “actuality” and others. An analysis of theories of Plotinus and Proclus on the “Life of Intellect” demonstrates that these philosophers developed different approaches in their attempts both to define the connection between notions of Being, Life, and Intellect and to explain the way in which this connection provides metaphysical background for the sensual appearances of life that we observe around us in nature. In most cases, however, their attempts to explain this connection provoke additional difficult questions.